Answer:
(p, q) = (4/10, 15/10) = (0.4, 1.5)
Explanation:
Apparently, you're to solve for q first. It is convenient to use the first equation for that purpose.
-4p +7q = 89/10
7q = 89/10 +4p . . . . . . add 4p to both sides
q = (89/10 +4p)/7 . . . . divide by the coefficient of q
Now, we have an expression we can substitute for q in the second equation:
-12p +35(89/10 +4p)/7 = 477/10
-12p +445/10 +20p = 477/10 . . . . . eliminate parentheses
8p = 32/10 . . . . . . . . . . . . . . . . subtract 445/10
p = 4/10 . . . . . . . . . . . . . . divide by 8
q = (89/10 +4(4/10))/7 = 105/(10·7) = 15/10
The solution is (p, q) = (0.4, 1.5).